Economics of milk processing in cooperative sector of Haryana - Singh, Ajmer Singh; Chandel, BS; Chauhan, AK; Das, Jagruti; KM, Ravishankara (Indian Journal of Dairy Science, 2021)
In the rural sector, dairying and milk production is an important economic activity and has become a secondary source of income and employment. Cooperatives play an important role in animal husbandry and dairying sector, which contributes about one-fourth of agricultural GDP of the country. This study works out the cost of collection, chilling and transportation to arrive at economics of milk processing and manufacturing of milk products in Haryana by selecting milk plants from different zones in the cooperative sector. The economics of milk processing in Haryana show that procurement cost was found to be higher in Western zone which was estimated to Rs. 1.83 per litre of milk compared to Rs. 1.67 per litre in Eastern zone. Out of which transport cost accounted for maximum share (54.57%) followed by transportation cost (54.5 7%), chilling cost (24%), collection cost (17.1 4%) and reception cost (8.57 %). The other higher profit giving products were double toned milk and ghee which yielded profit over cost of 15.21 and 11.88 percent respectively. These products were followed by ghee at 11.88%Â  (Rs. 39.54 per unit). The profit margin for paneer was found to be lowest at 7.76 % with cost of Rs 16.05 per kg. The information on the profitability of different products in HaryanaÂ  is useful tool for the management to reshuffle the product mix of the plants on the basis of cost of manufacturing, profits and demand of different products.